Doing research - Thomas, Gary, 1950- (Houndmills, Basingstoke, Hampshire : Palgrave MacMillan, 2011)
'This concise guide equips undergraduate students with the basic knowledge for doing research. Providing direct, practical advice, this well-presented book covers planning, groundwork, research design, fieldwork, analysis and writing up'--
Machine generated contents note: -- PART 1 Planning -- PART 2 Groundwork -- PART 3 Building a Scaffold -- PART 4 Fieldwork: Finding the Data -- PART 5 Analysing the Data -- PART 6 Writing up Research.
Includes bibliographical references and index.
Keywords: Research -- Methodology -- handbooks, manuals, etc; Report writing -- Handbooks, manuals, etc